Assessing emotional, empathic and coping skills in Spanish undergraduates in Health Sciences and Social Sciences - Martínez-Lorca, Manuela; Zabala-Baños, Mª Carmen; Morales Calvo, Sonia; Romo, Roberto Aguado; Martínez-Lorca, Alberto (Retos, 2023)
Background: Higher education is considered to be one of the phases in the life cycle that produces psychological distress and academic pressure. The aim of the study was to assess to assess the emotional, empathic and coping skills of undergraduate students of Health Sciences and Social Sciences undergraduates using an explorative approach in a cross sectional study.Methods: A sample of 693 first-to-fourth-year students enrolled in different degree courses. We used an “ad hoc” questionnaire, the Trait Meta-Mood Scale (TMMS-24), Trait Meta-Mood Scale (TMMS-24), The Interpersonal Reactivity Index (IRI) and Brief COPE.Results: We found higher scores in capacity for empathy using the IRI, in emotional intelligence by TMMS-24 and a good coping style and adaptive strategies measured on the COPE, however, emotion regulation scores in DERS were medium. We found interesting relationships between female, first-year course, sport, anxiety and degree course in empathy, emotional intelligence, adaptative strategies and emotional regulation.Conclusions: Preventive and train measures in emotional and psychosocial resources are needed in higher education to achieve the highest possible level of psycho- emotional well-being.Keywords: emotional intelligence, empathy, coping skills, subjective well-being, students.